THE DEVELOPMENT OF MANAGEMENT SCIENCE IN THE ANCIENT WORLD - Aripov Oybek Abdullayevich (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2022)
The article discusses the antiquity of management science. The development of management and the difference between the concepts of "management" and "management" are also theoretically justified.